2001
DOI: 10.1042/0264-6021:3560769
|View full text |Cite
|
Sign up to set email alerts
|

Amine oxidase substrates mimic several of the insulin effects on adipocyte differentiation in 3T3 F442A cells

Abstract: We have previously reported that substrates of monoamine oxidase (MAO) and semicarbazide-sensitive amine oxidase (SSAO) exert short-term insulin-like effects in rat adipocytes, such as stimulation of glucose transport. In the present work, we studied whether these substrates could also mimic long-term actions of insulin. Adipose differentiation of 3T3 F442A cells, which is highly insulin-dependent, served as a model to test the effects of sustained administration of amine oxidase substrates. Daily treatment of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 48 publications
(19 citation statements)
references
References 35 publications
2
17
0
Order By: Relevance
“…Here we show that SSAO activity from endothelial cells can also promote skeletal muscle glucose transport. In keeping with these observations it has previously been observed that SSAO substrates, including methylamine, promote in vitro insulin-like effects on adipocyte (2,6,7,32) and smooth muscle cell metabolism (3) through the production of hydrogen peroxide. This reactive oxygen species has been implicated in the insulin intracellular signaling pathway through its capacity to inhibit protein tyrosine phosphatase activity and hence enhance protein phosphorylation in response to insulin (33).…”
Section: Insulin Mimicrysupporting
confidence: 70%
“…Here we show that SSAO activity from endothelial cells can also promote skeletal muscle glucose transport. In keeping with these observations it has previously been observed that SSAO substrates, including methylamine, promote in vitro insulin-like effects on adipocyte (2,6,7,32) and smooth muscle cell metabolism (3) through the production of hydrogen peroxide. This reactive oxygen species has been implicated in the insulin intracellular signaling pathway through its capacity to inhibit protein tyrosine phosphatase activity and hence enhance protein phosphorylation in response to insulin (33).…”
Section: Insulin Mimicrysupporting
confidence: 70%
“…We and others have previously shown that SSAO activation promotes adipocyte maturation 8,35 and stimulates glucose transport through the GLUT transporters via H 2 O 2 in adipocytes 31 and VSMC 9 . Glucose is of major importance for the biosynthesis of matrix glycosaminoglycans, and for the maturation of chondrocytes 36e39 .…”
Section: Discussionmentioning
confidence: 85%
“…In addition to the receptor‐mediated action, 5‐HT also coordinates fat metabolism and feeding through a receptor‐independent mechanism (Srinivasan et al , 2008). Other reports described the association between MAO expression and insulin sensitization (Fontana et al , 2001) and that between MAO polymorphism and obesity (Fuemmeler et al , 2008). These reports suggested that 5‐HT metabolites are not simply degradation products of 5‐HT, but may have additional functions.…”
Section: Introductionmentioning
confidence: 99%